Mechanical Ventilation Boot Camp: A Simulation-Based Pilot Study. (1st February 2016) - Yee, Jennifer; Fuenning, Charles; George, Richard; Hejal, Rana; Haines, Nhi; Dunn, Diane; Gothard, M. David; Ahmed, Rami A.
Abstract : Objectives . Management of mechanically ventilated patients may pose a challenge to novice residents, many of which may not have received formal dedicated critical care instruction prior to starting their residency training. There is a paucity of data regarding simulation and mechanical ventilation training in the medical education literature. The purpose of this study was to develop a curriculum to educate first-year residents on addressing and troubleshooting ventilator alarms. Methods . Prospective evaluation was conducted of seventeen residents undergoing a twelve-hour three-day curriculum. Residents were assessed using a predetermined critical action checklist for each case, as well as pre- and postcurriculum multiple-choice cognitive knowledge questionnaires and confidence surveys. Results . Significant improvements in cognitive knowledge, critical actions, and self-reported confidence were demonstrated. The mean change in test score from before to after intervention was +26.8%, and a median score increase of 25% was noted. The ARDS and the mucus plugging cases had statistically significant improvements in critical actions, p < 0.001 . A mean increase in self-reported confidence was realized (1.55 to 3.64), p = 0.049 . Conclusions . A three-day simulation curriculum for residents was effective in increasing competency, knowledge, and confidence with ventilator management.